1997
DOI: 10.1007/bf02632324
|View full text |Cite
|
Sign up to set email alerts
|

Immunisation of cattle in Zimbabwe usingTheileria Parva (boleni) without concurrent tetracycline therapy

Abstract: Five hundred and ten cattle were immunised using the Theileria parva (Boleni) stock without concurrent chemotherapy with tetracycline on 2 farms in Zimbabwe, both of which had a history of theileriosis. The stabilate had been titrated in Friesian calves to determine a 50% protective dose (PD50) and 2 or 3 (PD50s) were used to immunise the cattle. None of the cattle showed a clinical reaction following the immunisation procedure. However, the cattle were shown to have responded immunologically on testing for an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…The present study showed that the cattle‐derived T. parva Boleni, used to immunize cattle in Zimbabwe,4 and a buffalo‐derived stabilate could both produce a carrier state in buffaloes. The carrier parasites were transmissible to cattle, with the buffalo‐derived stabilate producing fatal reactions.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…The present study showed that the cattle‐derived T. parva Boleni, used to immunize cattle in Zimbabwe,4 and a buffalo‐derived stabilate could both produce a carrier state in buffaloes. The carrier parasites were transmissible to cattle, with the buffalo‐derived stabilate producing fatal reactions.…”
Section: Discussionmentioning
confidence: 59%
“…The present paper shows the results of epidemiological observations carried out on two game parks in the Highveld of Zimbabwe regarding the infectivity of ticks collected from buffalo‐grazed pastures to cattle and the carrier‐state in buffaloes after infection with the T. parva Boleni stabilate. This stabilate was registered as a vaccine under the name Blovac for vaccination of cattle against theileriosis in Zimbabwe 4…”
Section: Introductionmentioning
confidence: 99%
“…the Boleni stock) may be somewhat less virulent than most stocks of classical ECF (although it can be quite virulent: Uilenberg et al 1982) and antigenic diversity in the bovis type appears to be much more limited. It is possible to immunize against the disease by administering a sublethal dose of sporozoites, without using tetracyclines (Kanhai et al 1997), even though earlier attempts suggested that this approach might be too risky . A possible explanation for these different results might be an irregular distribution (clumping) of sporozoites in stabilates in the earlier experiments.…”
Section: History Of Immunizationmentioning
confidence: 99%
“…This relationschip can be roughly evaluated through assessments of the clinical reactions of groups of cattle injected with serial dilutions of a stabilate. The immunization method developed in Zimbabwe (Kanhai et al 1997) is based on this principle.…”
Section: History Of Immunizationmentioning
confidence: 99%
“…It is disappointing, therefore, that 20 years have elapsed and little progress can be seen in the field application of immunization except in Zambia 2 and Zimbabwe. 3,4 This appears to be due to scientific and political opinion rather than technology. 5 Thus, most countries in Eastern and Central Africa remain totally dependent on tick control, which is very expensive and generally unsustainable.…”
Section: Introductionmentioning
confidence: 99%